CoDeMap: a classification scheme for benthic habitats from the coast to the deep sea in the Mediterranean and Black Sea - Grande, Valentina; Angeletti, Lorenzo; Prampolini, Mariacristina; Castellan, Giorgio; Dalla Valle, Giacomo; Fraschetti, Simonetta; Basso, Daniela; Berov, Dimitar; Bracchi, Valentina A.; Cardone, Frine; Chimienti, Giovanni; Falace, Annalisa; et al. (Frontiers in Marine Science, 2025)
The spatial representation of benthic habitats is essential across various applications, such as biodiversity monitoring, ecosystem management and conservation, and maritime spatial planning. In this context, classification schemes provide a universally understandable framework to characterize and chart the seafloor. This work introduces the Coast to Deep Mapping (CoDeMap) classification scheme for benthic habitats from the coast to the deep-sea environments. It consists of three main components (Morphology, Substrate and Biology) and it is conceived as a practical tool for users from various backgrounds who need to organize and interpret marine observational data, as well as characterize and map seafloors. While primarily developed for the Mediterranean Sea and the Black Sea, CoDeMap serves as a foundational framework that can be adapted to address any current or future similar request worldwide.